1992
DOI: 10.1084/jem.176.3.909
|View full text |Cite
|
Sign up to set email alerts
|

CD2-mediated autocrine growth of herpes virus saimiri-transformed human T lymphocytes.

Abstract: SummaryHerpes virus saimiri (HVS) immortalizes T lymphocytes from a variety of primates and causes acute T cell lymphomas and leukemias in nonnatural primate hosts. Here we have analyzed the requirements for growth of three HVS-transformed human T cell lines. The cells expressed the phenotype of activated T cells: two were CD4 + , and one was CD8 + . All three cells responded to all allogeneic human cell lines tested with enhanced proliferation, production of interleukin 2 (Ib2), and increased expression of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
49
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 13 publications
1
49
0
Order By: Relevance
“…16,17 Infection of human blood lymphocytes and thymocytes with strains of subgroup C, in contrast to the other subgroups, yields continuously proliferating T-cell lines. 18,19 Earlier publications have demonstrated that a selectable HVS has the ability to persist in a variety of human cell lines for long periods of time, apparently without the production of infectious progeny. 20,21 In this report, we describe our findings using a nontransforming wild-type (wt) virus carrying the enhanced green fluorescent protein (EGFP) and neomycin resistance (neo r ) marker genes.…”
mentioning
confidence: 99%
“…16,17 Infection of human blood lymphocytes and thymocytes with strains of subgroup C, in contrast to the other subgroups, yields continuously proliferating T-cell lines. 18,19 Earlier publications have demonstrated that a selectable HVS has the ability to persist in a variety of human cell lines for long periods of time, apparently without the production of infectious progeny. 20,21 In this report, we describe our findings using a nontransforming wild-type (wt) virus carrying the enhanced green fluorescent protein (EGFP) and neomycin resistance (neo r ) marker genes.…”
mentioning
confidence: 99%
“…In contrast to multiple reports on preserved functions, little is known about cellular features which are clearly changed after transformation. The most pronounced difference is a specific type of hyperreactivity to CD2 stimulation via cell-bound CD58 or cross-linked CD2 antibodies (33). Moreover, unusually high levels of gamma interferon are produced after stimulation, which shifts transformed T helper 2 cells to the T helper 0 phenotype (6).…”
mentioning
confidence: 99%
“…In the CD2 hyperreactivity test, 19,33 5 Â 10 4 transformed T cells were incubated alone or in the presence of an antibody and/or 5 Â 10 4 stimulator cells in 200 ml of complete RPMI 1640 medium in flat-bottom wells. The rat monoclonal antibody 39C1.5 (anti-CD2, Beckman Coulter, Krefeld, Germany), recognizing the human T11.1 CD2 epitope, was used in stimulation and blocking assays at 1 mg ml À1 .…”
Section: Cd2 Hyperreactivitymentioning
confidence: 99%
“…These virus mutants carry the hTERT expression cassette at the right end of the L-DNA and with or without the stpC/tip gene (orf1) at the left L-DNA end. As HVS-transduced T cells exhibit a few specific properties such as CD2 hyperreactivity, 33 elevated IL-26 34 and Lyn expression, 19,35 we analyzed the influence of the stpC/ tip deletion (Dorf1) on these properties and concluded that hTERT could not substitute them in this phenotype, although hTERT was functionally expressed after transduction. The interaction of StpC with Ras and tumor necrosis factor-associated factors leading to nuclear factorkB activation, in addition to the association of Tip with signal transducers activators of transcription and tipassociated protein, are crucial for the facilitated growth transformation of human T lymphocytes.…”
Section: Introductionmentioning
confidence: 99%